The Wiley-Blackwell companion to political sociology - Amenta, Edwin , 1957-; Nash, Kate , 1958-; Scott, Alan , 1956- (Wiley-Blackwell, 2012)
With contributions from an international, interdisciplinary group of leading scholars, The Wiley-Blackwell Companion to Political Sociology is a complete reference guide, reflecting the scope and quality of the discipline, and highlighting emerging topics in the field